An integrative literature review of the implementation of advance care planning in hospital settings. Issue 21 (19th May 2021) - Cerulus, Marie; Bossuyt, Inge; Vanderhaeghen, Birgit
Abstract: Aims and Objectives: To identify and synthesise existing literature about action research in the implementation of advance care planning in a hospital setting. Background: Despite the proven added value of advance care planning, there is a lack of wide integration of this concept. There are several obstacles known for the implementation but it remains unclear how these can be overcome. Action research is described in the literature as a plausible way to overcome obstacles to the implementation of quality enhancing projects. Design: An integrative literature review was conducted using the Preferred Reporting Items for Systematic Review and Meta‐Analysis (PRISMA) and reported in accordance with the PRISMA statement. Methods: We searched databases MEDLINE, EMBASE, CINAHL and Web of Science to identify executed action research for the implementation of advance care planning programs within a hospital setting, from January 2005 until November 2019. Studies were assessed for comprehensiveness and were supplemented by studies in reference lists of included articles. A quality appraisal and a thematic synthesis were performed on all included studies. Results: Five studies met inclusion criteria. Interventions focused on both nurses, physicians and hospitalised patients. Interventions targeted three different themes: identifying at‐risk patients, adapting documentation to the local context and using communication improvement tools. Conclusions: A Supportive and Palliative Care Indicators Tool is proposed to identify patients in need of advance care planning to work more efficiently. Furthermore, adapting documentation and instruments to a specific care context are shown to make advance care planning more effective. Communication challenges can be addressed by promoting communication skills and increase stakeholder self‐confidence.